Forming Self-Identity of Elementary School Children: The Relational Role of Family and Social Environment in the Context of Islamic Education - Muh Abham Maqbul By; Wahyu Iskandar (Yayasan Zia Salsabila, 2025)
This study examines the role of artificial intelligence (AI)-based learning media in shaping the self-identity of elementary school children, by highlighting the relational contribution of family and social environment in the context of Islamic education. The main problem lies in how AI can be used not only to improve learning outcomes, but also as a pedagogical instrument in strengthening children's character and self-identity expression. The purpose of this study is to explore the effectiveness of integrating AI media in the learning process and its impact on students' cognitive, affective, and social dimensions. This study uses a qualitative approach with a field study at State Elementary School 2 Konawe Selatan, supported by thematic analysis using the N-Vivo device. The results of the study indicate that AI media significantly improves conceptual understanding, multimodal communication skills, and forms students' self-identity that is more reflective, confident, and collaborative. In addition, AI also functions as a relational bridge between teachers, students, and parents. These findings provide important implications for the design of technology-based Islamic pedagogy as well as recommendations for curriculum development, teacher training, and future-oriented madrasah education policies.